Edukasi Gizi Seimbang untuk Pencegahan Stunting pada Anak Usia Dini: Pengabdian Masyarakat di TK Annur Anyer - Hidayat, Amat; Oktania, Sella; Siregar, Aulia Fatonah; Junariah, Siti Desti; Hasanah, Uswatun; Irmawati, Winda; Mustabsiroh, Mustabsiroh; Mulyati, Sri; Hermawati, Hermawati; Kusrini, Eni (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
Stunting in early childhood is a significant health problem in Indonesia, especially in rural areas. This community service aims to provide balanced nutrition education as an effort to prevent stunting in Annur Anyer Kindergarten, Serang Regency. The main targets of this program are parents and teachers, who play an important role in regulating children's daily diets. Education is provided through counseling on the importance of balanced nutrition, preparing nutritious food menus, and guidance in monitoring children's nutritional development. This activity also involves interactive discussion sessions and direct practice in designing daily menus that are suitable for early childhood. The results show an increase in knowledge and awareness of participants about the importance of proper nutritional intake and its impact on preventing stunting. With this advancement in knowledge, it is hoped that there will be changes in healthier eating patterns in the family and school environment, so that they can support efforts to prevent stunting in early childhood in the area.